Indonesia's Dispute Resolution in All England 2021 - Widhyasmaramurti Widhyasmaramurti; Alfan Rahadi; Poetrena Oneal (IAIN Salatiga, 2021)
All England is one of the oldest and famous badminton competitions in the world which experienced challenges during the Covid-19 pandemic in 2021. The forcing of Indonesian to withdraw from the event due to the National Health Service (NHS) regulations led to a dispute between the Badminton World Federation (BWF) as the organizer to the Indonesian Badminton Squad. The situation becomes complicated when the media creates a narrative that triggers a bigger conflict due to public pressure through social media, which causes Indonesian government to intervene. This study aims to explain the dispute resolution through negotiation and its factors. The method in this study is qualitative descriptive with literature review and interview. Based on data from online media news, the research results show Indonesian dispute resolution in All England cannot achieve a Win-Win solution since state policy is above everything. The factors of the negotiation process come from the internal, external, and cultural factors.